Sonography of Morton Neuromas: What Are We Really Looking At?. (1st October 2016) - Cohen, Stuart L.; Miller, Theodore T.; Ellis, Scott J.; Roberts, Matthew M.; DiCarlo, Edward F.
Abstract : Objectives: To determine what accounts for the sonographic appearance of a Morton neuroma by correlating preoperative sonograms with the sonographic appearance of the resected surgical specimen, the surgical findings, and the pathologic examination. Methods: Ten Morton neuromas that had preoperative sonograms underwent postoperative specimen sonography and histologic evaluation. The appearance and size of the neuromas were compared between the preoperative and postoperative specimen images and were compared to the surgical and pathologic appearances. Results: Preoperative images showed a fibrillar echogenic nerve coursing into a heterogeneous hypoechoic mass measuring 14.3 mm in average length (range, 9.0–24.0 mm) that contained a round, mildly echogenic mass within it measuring 7.6 mm in average length (range, 4.5–12.0 mm). Surgically, the specimens showed scarred intermetatarsal bursas and tangled vessels surrounding the nerve. Specimen sonography showed echogenic focal enlargement of the nerve at the site of the neuroma, measuring 6.8 mm in average length (range, 3.5–11.0 mm). The size of the resected neuroma was smaller than the hypoechoic mass on the presurgical images ( P < .001). Within the hypoechoic mass, the small echogenic focus showed no difference in size compared to the specimen ( P = .40), but the shape of the echogenic specimen was fusiform, whereas the preoperative appearance was round. Histologically, the resected specimens showed sclerosis and mucoid degeneration of the nerve fascicles and fibrotic thickening of the perineurium. Conclusions: The hypoechoic heterogeneous mass that is referred to as a Morton neuroma sonographically is really a "neuroma‐bursal complex" that is much larger than the actual neuroma itself.